2019
DOI: 10.1016/j.neuroimage.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Modulations in resting state networks of subcortical structures linked to creativity

Abstract: Creativity is a sine qua non ability for almost all aspects of everyday life. Although very profound behavioural models were provided by 21th century psychologists, the neural correlates of these personality features associated with creativity are largely unknown. Recent models suggest strong relationships between dopamine release and various creative skills. Herein, we employed functional connectivity analyses of resting-state functional magnetic imaging data in order to shed light on these neural underpinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…In these studies, the reported activations were registered during a creative task and were therefore specific to this task. Some works have also used a global approach to investigate differences between high-and lowcreative people using raw scores by studying brain connectivity at rest (Beaty, Kenett, et al, 2018;Beaty et al, 2019;Belden et al, 2020;Cousijn et al, 2014;Feng et al, 2019;Kenett et al, 2020;Schuler et al, 2019). The brain at rest is always activated, with some regions being coactivated at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the reported activations were registered during a creative task and were therefore specific to this task. Some works have also used a global approach to investigate differences between high-and lowcreative people using raw scores by studying brain connectivity at rest (Beaty, Kenett, et al, 2018;Beaty et al, 2019;Belden et al, 2020;Cousijn et al, 2014;Feng et al, 2019;Kenett et al, 2020;Schuler et al, 2019). The brain at rest is always activated, with some regions being coactivated at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Peterson and colleagues (2002) found that behavioural inhibition is a gating process that allows ignoring prior related information; individuals with decreased behavioural inhibition are more likely to develop their creative potential. However, it is worth noting that previous studies have drawn attention to fronto-striatal pathways underlying dopaminergic modulation of creativity (Boot et al, 2017;Schuler et al, 2019), which is an "association" loop passing through the prefrontal cortex, association areas, and caudate nucleus (another part of the striatum) (Alexander, Delong & Strick, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the "motor" loop pathways may be a result of other neuromodulators, such as noradrenaline and oxytocin. Although previous studies have focused on dopamine (fronto-striatal pathway) as the key neurotransmitter involved in creative thinking (Boot et al, 2017;Schuler et al, 2019), cognition and behaviour are modulated by other neurotransmitters such as noradrenaline (Aston-Jonnes and Cohen, 2005;Berridge and Waterhouse, 2003), in addition to dopamine. Noradrenaline is thought to modulate the balance between exploitation and exploration by promoting stabilization of salient information in working memory and in attention shifting (Aston-Jonnes and Cohen, 2005;Berridge and Waterhouse, 2003) and may enable the persistence of creative thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 36 papers on the general creative thinking process employed RAT. Studies on the general creative thinking process explored how the incubation mechanism (such as sleep, fixation, inhibition, and dreaming) affects creative thinking (Zhong et al, 2008;Sio et al, 2013;Smith et al, 2013;Koppel and Storm, 2014;Whitehurst et al, 2016;Carlsson et al, 2019), how individuals' memory, such as working memory and memory retrieval, affects creative thinking (Ricks et al, 2007;Dewhurst et al, 2011;Storm et al, 2011;Gómez-Ariza et al, 2017;Beda and Smith, 2018;Wang et al, 2019), how attention span enhances the output of creative ideas (Ansburg and Hill, 2003;Schmajuk et al, 2009;Zmigrod et al, 2015;Wronska et al, 2018), the association between creative thinking and how the brain works (such as brain networks, brain structure, brain function, and brain waves) (Razumnikova, 2007;Cerruti and Schlaug, 2009;Brunyé et al, 2015;Aberg et al, 2017;Godwin et al, 2017;Colzato et al, 2018;Dong, 2018;Hertenstein et al, 2019;Li et al, 2019;Peña et al, 2019;Schuler et al, 2019), and how priming (Moss et al, 2011;Chiu and Tu, 2014;Radel et al, 2015;Baror and Bar, 2016), metacognition (Ackerman and Beller, 2017), analogy (Jones and Estes, 2015), colors (Xia et al, 2016), genes (Han et al, 2018), and intelligence (Mussel et al, 2015) inf...…”
Section: General Creative Processmentioning
confidence: 99%